Post-Operative Infections in Patients After Extraction of Impacted Third Molar by Different Flap Designs - Yousaf, Fatima; Javed, Tariq; Najm, Eram; Najeeb, Humna; Naz, Fahwa; Tahir, Fatima (Indus Journal of Bioscience Research, 2025)
Introduction: One of the biggest worries for most surgeons doing impacted dental operations is post-surgery infection. This study’s objective is to ascertain the prevalence of post-operative infections in patients having their impacted third molar removed using various flap designs and suturing techniques. The findings of this study will help surgeons choose flap designs and biomaterials more effectively, reducing the risk of infection and maybe speeding up the healing process for patients. Study type: Descriptive, cross sectional study. Settings: Department of Oral and Maxillofacial Surgery, Madinah Teaching Hospital, Faisalabad. Study duration: January 2025 to May 2025. Materials & Methods: Total 437 patients between the ages of 18 and 60 undergoing third molar extraction were included. Patients with severe medical conditions, women who were pregnant or nursing, smokers, and those using drugs that affect the healing of wounds after surgery were excluded. Oral and maxillofacial surgeons carried out the operations. An injection of local anesthesia was made. Blade number fifteen was used to raise the designated flap (envelope or triangular). Hemostasis was attained. After the tooth was fully extracted and thoroughly irrigated with 0.9% normal saline, the flap was sutured using the appropriate suture material (both absorbable and nonabsorbable). Postoperative instructions were provided, and a little gauze pack was applied to the area. On the seventh postoperative day, the suture was taken out, and a postoperative infection was observed (painful induration and purulent discharge at the surgical site). Results: Age range in this study was from 18 to 60 years with mean age of 36.95 ± 11.60 years. Majority of the patients 254 (58.12%) were between 18 to 40 years of age. Out of 437 patients, 79 (18.08%) were male and 358 (81.92%) were females with male to female ratio 1:4.5. Mean duration of surgery in our study was 27.88 ± 7.0 minutes. In our study, frequency of post-operative infections in patients undergoing removal of impacted third molar was found in 34 (7.78%) patients. Conclusion: This study found no statistically significant association between the presence of post-operative infection and any of the other risk factors, with the exception of flap design.